Paradigm Shifts in Internalization of International Law: A Case Study of Growing Human Rights Jurisprudence in Nepal - Pathak, Geeta (Kathmandu School of Law Review, 2018)
The concept of internalization (domestication) of international law, underpinning the traditional theories of ‘monism and dualism,’ is being shifted along with the change in the contexts. Internalization can be mapped out through the process and result indicators of recognition of international legal norms through incorporation or transformation in the domestic laws, including the Constitution. The success of the internalization of international human rights law depends on the political will of the government and independent judiciary. The state practices, including decisions of the courts, discussed in this paper, further indicate the eventual changes in the process. Most importantly, the level of internalization can be measured by jurisprudential trends of application of international law in general and the international human rights instruments in particular. The second part of this paper minutely observes the ’bramble-bush effects’ on the laws and jurisprudence developed along with democratization in Nepal since 1990. Nepal is an interesting case study due to its experiment of the theories of monism and dualism. Although the Treaty Act of Nepal explicitly recognizes the higher legal status of international agreements or treaties to which Nepal is a party, the Constitution of Nepal does not recognize the same. Nevertheless, the situation of ratification and accession of a large number of human rights treaties without reservation and growing thematic human rights jurisprudence reasonably justify the greater scope of internalization of international human rights laws in Nepal. DOI: https://doi.org/10.46985/jms.v6i2.209